A modern nerd's guide to comic books - Horning, Nicole (Geek out!, 2020)
Briefly explores the history comic strips and books and the fandom that has arisen around them, covering some of the genre's most famous characters and creators--from Spider-Man to Charlie Brown. Includes a glossary.